Integrating Culturally Responsive Pedagogy to Enhance Inclusive Classroom Practices in Multilingual Schools - Abhay Pandey (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Multilingual schools increasingly reflect complex intersections of language, culture, and educational equity, presenting persistent challenges for inclusive classroom practices. This study examines how culturally responsive pedagogy can be integrated to enhance inclusion within multilingual educational settings through a qualitative library-based research approach. Drawing on peer-reviewed literature addressing culturally and linguistically responsive teaching, inclusive pedagogy, and multilingual education, the study employs thematic content analysis to synthesize conceptual frameworks, empirical findings, and instructional implications. The findings reveal that culturally responsive pedagogy strengthens inclusive classroom practices by validating learners’ cultural identities, leveraging linguistic diversity as pedagogical capital, and aligning curriculum, interaction, and assessment with learners’ lived experiences. Evidence across studies indicates improved learner engagement, equitable participation, and more accurate representations of student competence when culturally responsive practices are systematically applied. The study concludes that culturally responsive pedagogy serves as a critical foundation for sustainable inclusion in multilingual schools, requiring coherent instructional design, reflective teacher practice, and institutional support to ensure equitable educational opportunities for all learners.